Peranan Lembaga Keuangan Syariah Dalam Ketersediaan Modal Usaha Berbasis Syariah Untuk Peningkatan Ekonomi Usaha di Daerah Sleman - Hilmi Naufal Muzakky; Darmawan (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research discusses the role of Islamic financial institutions (LKS) in providing Sharia-based business capital to enhance local business economy in Sleman District. Through a qualitative approach focusing on interviews and literature studies, this research explores the perspectives of business actors and community leaders regarding the role of LKS in empowering micro, small, and medium-sized enterprises (MSMEs) based on Sharia principles. The research findings indicate that LKS plays a crucial role in providing Sharia-compliant financing access, supported by education and financial management guidance. However, there are still challenges such as the complexity of the financing process that requires simplification. Therefore, close cooperation is required among LKS, local government, and the community to overcome these obstacles, through innovations such as technology-based financing platforms, training and mentoring programs, and enhancement of Sharia financial literacy. Through the proposed suggestions, it is hoped that the role of LKS in empowering Sharia-based MSMEs in Sleman District can be further strengthened, supporting local economic growth and improving overall community well-being.